Situating Cognition: Knowledge and Power in Context - Catherine A. Hansman; Arthur L. Wilson (Adult Education Research Conference, 2002)
Although adult education as a field has shown interest in the work of Lave and others concerning situated cognition, the authors argue that adult education as a field has misappropriated some of the central concepts of situated cognition.